This Time is Different? - On the Use of Emergency Measures During the Corona Pandemic - Christian Bjørnskov; Stefan Voigt (University of Hamburg, Institute of Law and Economics (ILE), 2020)
The COVID-19 pandemic has not only caused thousands to die and millions to lose their jobs, it has also prompted more governments to simultaneously to declare a state of emergency than ever before. States of emergency usually imply the extension of executive powers that diminishes the powers of other branches of government, as well as to the civil liberties of individuals. Here, we analyze whether the use of emergency provisions during the COVID-19 pandemic is an exception, and find that this is not the case. In fact, some measures point at long-term dangers to the rule of law and democracy.
Keywords: K40; Z13; 320; COVID-19; constitutional emergency provisions; state of emergency